Biện pháp sử dụng trò chơi học tập phát triển kĩ năng đọc cho trẻ mẫu giáo 5-6 tuổi - Phạm , Thị Thu; Trịnh , Thị Thu Hương; Phạm, Thị Lê Hoàn (Tạp chí Giáo dục, 2024)
Preparing children to be ready for the 1st grade is an important task of Preschool Education, which prepares children with reading and writing skills to create a good start to help them be confident and successful in learning. Older preschoolers are an important age; at the end of that age, children must go through a transitional turning point, when transferring from the main activity of playing to learning activities. Therefore, helping children develop reading skills through learning games is an effective way, suitable for children's learning characteristics as well as educational goals. The article has proposed three measures to use learning games to develop reading skills for children: (1) Choosing learning games that meet the goal of developing reading skills for 5-6 years old preschool children; (2) Designing and organizing learning games to develop reading skills; (3) Creating a language-rich learning environment to develop children's reading skills. These measures are suggestions that teachers can use and adjust depending on the local context, classroom, and children's characteristics.